EM wave propagation analysis in plasma covered radar absorbing material - Singh, Hema; Antony, Simy; Rawat, Harish Singh (Springer, 2016)
This book focuses on EM propagation characteristics within multilayered plasma-dielectric-metallic media. The method used for analysis is impedance transformation method. Plasma covered radar absorbing material is approximated as a multi-layered dielectric medium. The plasma is considered to be bounded homogeneous/inhomogeneous medium. The reflection coefficient and hence return loss is analytically derived. The role of plasma parameters, such as electron density, collision frequency, plasma thickness, and plasma density profile in the absorption behavior of multi-layered plasma-RAM structure is described. This book provides a clearer picture of EM propagation within plasma. The reader will get an insight of plasma parameters that play significant role in deciding the absorption characteristics of plasma covered surfaces.
Keywords: Electromagnetic waves.; Plasma waves.; elektronické knihy; electronic books